2020
DOI: 10.3390/jcm9061768
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Blood Flow Changes Impact Visual Acuity Gain after Surgical Treatment for Idiopathic Epiretinal Membrane

Abstract: Background: Idiopathic epiretinal membrane (iERM) is a common eye disease, which can be treated by surgical removal of the fibrotic tissue. Morphological outcome is generally evaluated by optical coherence tomography (OCT). Here, we investigate the impact of surgery on hemodynamics of the posterior pole, using OCT angiography (OCTA). Methods: Patients with unilateral iERM and indication for treatment were included. OCT and OCTA images of the posterior pole were obtained preoperatively and 3-months after 23G vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
(53 reference statements)
0
18
1
Order By: Relevance
“…Although it is still difficult to study the alteration of the deep capillary plexus in patients with ERM because of several artifacts, we cannot completely exclude the presence of vascular impairment of the deep capillary plexus preoperatively, which is located near the inner and outer borders of the INL in the parafoveal regions. Furthermore, Rommel et al [ 31 ] showed significant choroidal sublayer perfusion changes postoperatively for ERM with an increase perfusion of choriocapillaris and a decrease perfusion of Sattler’s layer, by using OCT angiography. Additionally, preoperative Sattler’s layer perfusion was suggested as a useful predictive marker for functional results, since a significant correlation was found with postoperative visual function [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is still difficult to study the alteration of the deep capillary plexus in patients with ERM because of several artifacts, we cannot completely exclude the presence of vascular impairment of the deep capillary plexus preoperatively, which is located near the inner and outer borders of the INL in the parafoveal regions. Furthermore, Rommel et al [ 31 ] showed significant choroidal sublayer perfusion changes postoperatively for ERM with an increase perfusion of choriocapillaris and a decrease perfusion of Sattler’s layer, by using OCT angiography. Additionally, preoperative Sattler’s layer perfusion was suggested as a useful predictive marker for functional results, since a significant correlation was found with postoperative visual function [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Rommel et al [ 31 ] showed significant choroidal sublayer perfusion changes postoperatively for ERM with an increase perfusion of choriocapillaris and a decrease perfusion of Sattler’s layer, by using OCT angiography. Additionally, preoperative Sattler’s layer perfusion was suggested as a useful predictive marker for functional results, since a significant correlation was found with postoperative visual function [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Manual segmentation (F.R.) was performed to get 20 µm slabs of the choriocapillaris (CC), Sattler's layer (SL) and Haller's layer according to previously published protocols [3,17,[19][20][21] (Figure 1D-F).…”
Section: Methodsmentioning
confidence: 99%
“…OM in turns of compression and decompression is still a treatment option for acute occlusions of retinal arteries, with the intention of inducing IOP fluctuations and retinal arterial dilatation, although evidence is lacking [11][12][13][14]. The development of optical coherence tomography angiography (OCTA) enables the assessment of the retinal and choroidal vascular network in vivo and in real time by creating slab-segmented angiograms in a noninvasive fashion [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic factors that have been reported include best-corrected visual acuity (BCVA), central retinal thickness (CRT), pseudohole, cystoid macula edema, intact photoreceptor inner and outer segments, location of ERM, and ocular perfusion. 3 , 5 , 13 In this study, we report the functional and anatomical outcomes of the MIVS using WAVS in fovea-attached type ERM. In addition, we discuss the prognostic factors which contribute to better visual improvement.…”
Section: Introductionmentioning
confidence: 99%